Prevalence of post-traumatic stress disorder and validity of the Impact of Events Scale – Revised in primary care in Zimbabwe, a non-war-affected African country. Issue 2 (16th March 2023) - Abas, Melanie A.; Müller, Monika; Gibson, Lorna J.; Derveeuw, Sarah; Dissanayake, Nirosha; Smith, Patrick; Verhey, Ruth; Danese, Andrea; Chibanda, Dixon
Abstract : Background: A critical step in research on the epidemiology of post-traumatic stress disorder (PTSD) in low-resource settings is the validation of brief self-reported psychometric tools available in the public domain, such as the Impact Event Scale – Revised (IES-R). Aims: We aimed to investigate the validity of the IES-R in a primary healthcare setting in Harare, Zimbabwe. Method: We analysed data from a survey of 264 consecutively sampled adults (mean age 38 years; 78% female). We estimated the area under the receiver operating characteristic curve and sensitivity, specificity and likelihood ratios for different cut-off points of the IES-R, against a diagnosis of PTSD made using the Structured Clinical Interview for DSM-IV. We performed factor analysis to evaluate construct validity of the IES-R. Results: The prevalence of PTSD was 23.9% (95% CI 18.9–29.5). The area under the curve for the IES-R was 0.90. At a cut-off of ≥47, the sensitivity of the IES-R to detect PTSD was 84.1 (95% CI 72.7–92.1) and specificity was 81.1 (95% CI 75.0–86.3). Positive and negative likelihood ratios were 4.45 and 0.20, respectively. Factor analysis revealed a two-factor solution, with both factors showing good internal consistency (Cronbach's factor-1 α = 0.95, factor-2 α = 0.76). In a post hoc analysis, we found the brief six-item IES-6 also performed well, with an area under the curve of 0.87 and optimal cut-off of 15. Conclusions: The IES-R and IES-6 had good psychometric properties and performed well for indicating possible PTSD, but at higher cut-off points than those recommended in the Global North.